Cultural Heritage in Education: Flamenco as a Pedagogical Tool for Future Teachers in Spain - Jesús Heredia-Carroza; Laura Díaz-Reyes; Daniela-Tatiana Agheorghiesei; Raluca Stoica (Heritage)
This study explores how future teachers in Spain perceive the incorporation of cultural heritage in education, with a specific focus on flamenco as a pedagogical tool. Using exploratory factor analysis and surveys from 301 participants, the research identified the key variables that influence the valuation of cultural heritage through flamenco within educational settings. The findings revealed that social and cognitive skills, such as group cohesion, attention, and memory, are significant factors in appreciating flamenco as an educational resource. The study emphasizes flamenco’s potential to foster emotional, social, and cognitive development, positioning it as an effective means to integrate cultural heritage into teaching practices. This research contributes to understanding how flamenco as a pedagogical tool can enrich educational methodologies and enhance cultural heritage awareness among future educators.